MENYOAL HADIS PEREMPUAN SEBAGAI FITNAH: ANTARA PEMAHAMAN TEKSTUAL DAN KONTEKSTUAL - Gusnanda; Hanifatul Husna (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This article discusses the misogynist hadith in Islam. The topic is interesting and important to discuss because the understanding of these traditions has an impact on the understanding and stigma of certain people or communities in viewing the social status of women in the public sphere. Mistakes in understanding these traditions often occur due to the use of inappropriate methodologies. For some groups, this hadith is considered as a form of misogynism and cornering women. Such a paradigm is certainly contrary to the basic principles of Islam that safeguard the dignity of women. The author seeks to explore an appropriate methodology to understand the hadith of women as